Reduction of diesel exhaust emission by using first stage seawater spray system - Mohd Azmi, Sitam (2012)
Air pollution from the diesel exhaust emission gives a bad effect to health and environment around the world. The content of the emission mostly harmful gases such as Nitrogen Oxide (NOx), Carbon Monoxide (CO), Hydrocarbon (HC) and Particulate Matter (PM). This thesis is aim to reduce diesel exhaust emission by using first stage seawater spray system. A spray chamber designed to setup together with the diesel engine for diesel experiment. The chamber is connected to the exhaust manifold to collect emission gas by using particle trap. Then, the emission data without seawater (WOS), with seawater (WS), and with electrolyzed seawater (WES) spray system for five variable engine speeds is analyzed using exhaust gas analyzer. The temperature change is also measured. The result had shown the comparison of emission concentration for three condition seawater sprays system in form of graph of emission concentration versus engine speeds. Most of the emission is reduce after flow through the spray chamber except for the oxygen that is increasing because of the additional oxygen in the seawater. The other emission is absorb by the alkaline seawater and dissolved in the seawater. The research had shown the effectiveness of alkaline seawater as a medium to reduce diesel exhaust emission. The emission WES spray is reducing more compares WS spray system. Furthermore, this research would also plan to add crank angle sensor on the engine to measure engine performance and study on content of waste seawater of this system.